The Effect of Corporate Image and Product Quality on Loyalty Mediated by Satisfaction: A Case Study on Savings Customers of PT. BPR BKK Jepara (Perseroda) - Sri Wulandari Wulandari; Endang Tjahjaningsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Customer loyalty is one of the elements to achieve bank profitability. This study aims to analyze the influence of corporate image, product quality and satisfaction on loyalty. The number of samples in this study was 112 respondents in savings products. Sampling used purposive sampling with the criteria being customers at the operational head office, customer age > 17 years, length of service as a customer for more than 2 years and having at least 2 accounts at PT BPR BKK Jepara (Perseroda). Data analysis techniques include descriptive statistics, instrument testing and multiple linear regression analysis tests, mediation tests using the Sobel test. The results of the data analysis obtained that corporate image has a significant positive effect on satisfaction, product quality has a significant positive effect on satisfaction, corporate image does not affect loyalty, product quality has a significant positive effect on loyalty, satisfaction has a significant positive effect on loyalty. The results of the mediation test obtained that although corporate image does not directly affect loyalty, it can affect loyalty through satisfaction mediation. Product quality affects loyalty through satisfaction mediation.